Kontrowersje wokół społecznego modelu niepełnosprawności - Twardowski, Andrzej (Kultura-Społeczeństwo-Edukacja, 2020)
Twardowski Andrzej, Controversies around the social model of disability. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 7–21, Adam Mickiewicz University Press. ISSN 2300-0422. DOI: 10.14746/kse.2019.16.1 The aim of the article is to present a critical analysis of the social model of disability. In the first part, the author discusses the genesis, essence and basic advantages of the social model of disability. Next, five major disadvantages of this model are analysed:/1/ avoiding dealing with impairment as an important aspect of the lives of people with disabilities, /2/ separating impairment from disability, /3/ assuming that all people with disabilities are exposed to social oppression, /4/ postulating the creation of an environment without barriers and /5/ assuming that disability is the basis of the identity of people affected by it. In the final part of the article, the author presents reflections on the possibility of creating a new, more holistic model of disability.